The Housing Problem in Great Cities - Gould, E. R. L. (Quarterly Journal of Economics, 1900)
Journal Article The Housing Problem in Great Cities Get access E. R. L. Gould E. R. L. Gould Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 14, Issue 3, May 1900, Pages 378–393, https://doi.org/10.2307/1882565 Published: 01 May 1900